Leadership of the Principal as Supervisor in Improving Teacher Performance at SMPN 10 Mataram - Fahrizal M Ismail; Sawaludin Sawaludin; Lalu Sumardi (CV. Rayyan Dwi Bharata, 2024)
The principal's leadership as a supervisor plays an important role in improving teacher performance at SMPN 10 Mataram. This research aims to examine how school principals' supervision practices can improve teacher performance. This research uses a qualitative approach with a case study method. Data collection techniques include observation, interviews and documentation. Research findings show that school principals implement several effective supervision strategies, including providing constructive feedback, organizing training and workshops, and providing intensive guidance in planning and implementing learning. In addition, effective leadership is demonstrated through good communication skills, creating a conducive work environment, as well as motivating and rewarding teachers. This research concludes that the principal's supervisory leadership significantly contributes to improving teacher performance, which ultimately has a positive impact on the quality of education at SMPN 10 Mataram